The Role of Military institution in the Nigerian Political life (Journal of the College of Education for Women, 2019)
The intervention in the military institute represents a great role in the Nigerianpolitical life since 1960. There are many reasons behind this domination. The First is thatmany African militants participated in liberating their countries from colonization. Thesecond is that they tried to stay in power as long as they could stay through the rule of oneparty.There fore, they depend on the process of political and economic reform to get rid ofmilitary rule that dominated the Nigerian Political life to be a civilian state